AN INFLUENCE ANALYSIS: INTELLECTUAL CAPITAL, CORPORATE GOVERNANCE, AND SUSTAINABILITY REPORTS ON FIRM VALUE OF ENERGY SECTOR COMPANIES LISTED ON THE IDX (2021-2024) - Rani Zahra; Zul Azmi; Wira Ramashar (Universitas Muhammadiyah Bengkulu, 2025)
This study aims to analyze the influence of intellectual capital, corporate governance, and sustainability reports on company value in the energy sector listed on the Indonesia Stock Exchange (IDX) during the period 2021–2024. The research employs a quantitative approach using multiple linear regression on secondary data derived from annual reports and company sustainability reports. The sample comprises 203 observations after undergoing data transformation and filtering processes. Corporate governance is measured primarily through institutional ownership and the presence of an independent board of commissioners. The results indicate that institutional ownership has a positive and significant impact on company value, whereas intellectual capital, independent boards of commissioners, and sustainability reports do not exhibit a significant effect. The lack of significant influence from independent boards of commissioners may be attributed to suboptimal oversight functions. Furthermore, these findings suggest that the efficiency of intellectual capital management and the quality of sustainability reporting have yet to become key factors in the market’s evaluation of the energy sector. Therefore, this study recommends that energy companies enhance their intellectual capital management and improve the quality of their sustainability reporting, while also strengthening the role and effectiveness of independent boards of commissioners to support the enhancement of company value